EFEKTIFITAS TERAPI BEKAM BASAH TERHADAP PENURUNAN KADAR ASAM URAT DI WILAYAH KERJA PUSKESMAS CILEGON - Rina Sumartini; Arif Susila (Universitas Mitra Indonesia, 2021)
Gout is the disease associated with hyperuricemia, hyperuricemia is a serum uric acid level of more than 7 mg / dl in men and more than 6 mg / dl in women. The purpose of this study was to determine the effectiveness of wet cupping therapy to reduce uric acid levels. The study design used one group pre test - post test with the number of respondents as many as 20 people. The results showed that the average uric acid level of respondents before wet cupping therapy was 9.7 while the average uric acid level after wet cupping therapy was 4.9. The results of bivariate analysis showed that the p value was 0.00 so that there was an effect of wet cupping therapy on the decrease in uric acid levels. It is hoped that the results of this study will become the basis for selecting alternative treatment methods in reducing uric acid levels